Wave disturbances over Indian Ocean area during drought and normal summer monsoons - RAO, G. APPA; PISAL, V. K. (MAUSAM, 1984)
Analysis has been carried out to study the tropospheric wave disturbances over the Indian Ocean area during two contrasting summer monsoon periods. The study reveals two significant waves with periodicity of 2 to 3 and 4 to 6 days in meridional wind component. These waves move westward with a wave length of about 20° and 32° respectively. The wave activity, in general, is stronger during the normal monsoon year than the drought year.